2012
DOI: 10.1371/journal.pone.0041865
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Is a Natural Extrahepatic Inhibitor of the PCSK9-Induced LDL Receptor Degradation

Abstract: Proprotein convertase subtilisin/kexin-9 (PCSK9) enhances the degradation of hepatic low-density lipoprotein receptor (LDLR). Deletion of PCSK9, and loss-of-function mutants in humans result in lower levels of circulating LDL-cholesterol and a strong protection against coronary heart disease. Accordingly, the quest for PCSK9 inhibitors has major clinical implications. We have previously identified annexin A2 (AnxA2) as an endogenous binding partner and functional inhibitor of PCSK9. Herein, we studied the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 84 publications
3
98
0
Order By: Relevance
“…CLEC810, InterScience). Circulating mouse Pcsk9 was immunoprecipitated and analyzed by Western blotting, as described previously (24). Total SREBP-2 was immunoprecipitated from 1 mg of protein (1:500; provided by Dr. Park) together with 50 l of protein A/G PLUS-agarose (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…CLEC810, InterScience). Circulating mouse Pcsk9 was immunoprecipitated and analyzed by Western blotting, as described previously (24). Total SREBP-2 was immunoprecipitated from 1 mg of protein (1:500; provided by Dr. Park) together with 50 l of protein A/G PLUS-agarose (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that annexin A2 is a natural extrahepatic inhibitor of PCSK9 110 and that in Anxa2-knockout mice, plasma PCSK9 doubles and LDLR decreases by ≈50% in some extrahepatic tissues, such as adrenals, small intestine, and colon but not in liver. 111 In addition, transgenic mice expressing human PCSK9 mainly in the kidney resulted in LDLR degradation mostly in the liver but not in adrenals. 112,113 Thus, it is probable that the high levels of annexin A2 in adrenals are responsible for the refractoriness of the LDLR in this tissue to the action of PCSK9.…”
Section: Adrenals and Kidneysmentioning
confidence: 99%
“…112,113 Thus, it is probable that the high levels of annexin A2 in adrenals are responsible for the refractoriness of the LDLR in this tissue to the action of PCSK9. 110,111 Another, not mutually exclusive, possibility is that in refractory tissues, such as the adrenals, the complex [PCSK9≡LDLR] enters endosomes but does not traffic to lysosomes and may actually recycle back to the cell surface. Accordingly, a possible explanation for the tissue-specific activity of PCSK9 could be that extrahepatic tissues that do not respond to PCSK9 are unable to sort the [PCSK9≡LDLR] complex to lysosomes, likely because of unfavorable cellular response or absence of functional specific protein(s) that control lysosomal targeting of the complex (Figure 2).…”
Section: Adrenals and Kidneysmentioning
confidence: 99%
See 2 more Smart Citations